Solvation free energies in [bmim]-based ionic liquids: anion effect toward solvation of amino acid side chain analogues - Mohammad Latif, Muhammad Alif; Micaelo, Nuno M.; Abdul Rahman, Mohd Basyaruddin (Elsevier, 2014)
Stochastic molecular dynamics simulations were performed to investigate the solvation free energy of 15 neutral amino acid side chain analogues in aqueous and five, 1-butyl-3-methylimidazolium ([BMIM])-based ionic liquids. The results in aqueous were found highly correlated with previous experimental and simulation data. Meanwhile, [BMIM]-based RTILs showed better solvation thermodynamics than water to an extent that they were capable of solvating molecules immiscible in water. Non-polar analogues showed stronger solvation in hydrophobic RTIL anions such as [PF6]− and [Tf2N]− while polar analogues showed stronger solvation in the more hydrophilic RTIL anions such as [Cl]−, [TfO]− and [BF4]−.